Urbanization and Slum Residential Area in Cities: a Theoretical Review - Muhammad Musiyam (Forum Geografi, 1991)
This paper aims to explain the inter relationship between urbanization and slum and squatter settlement phenomena in urban areas, focusing on two cases in Jakarta and Yogyakarta. Marginality theory and dependence theory are to explain the two phenomena above, because these theories have different assumption and different explanations about slum areas. Thus, the solutions offered are different too. The result of Tadjuddin and Taylor research into the slum and squatter settlement in Yogyakarta and Jakarta suggest that the phenomena of the slum settlement in this cities could not be explained by a single theory, either marginality theory or dependence theory.